The pressurized oxycombustion behavior of turkish lignites in the bubbling fluidized bed combustor - (:unkn) unknown (International Pittsburgh Coal Conference, 2020)
In this study, the combustion of two different Turkish lignites in a 30 kW thermal capacity of bubbling fluidized bed combustion system was carried out in order to compare their combustion characteristics in the air, atmospheric oxyfuel and pressurized oxyfuel environments. The combustor has 120 mm inner diameter, 2250 mm height (from distributor plate), and double layer refractory. The moisture, ash and volatile matter contents of the lignites were in the range of 16-36%, 30-31% and 6-27%, respectively. Combustor was operated in the temperature range of 745-855 °C, 760-835 °C and 750-860 °C air, atmospheric oxycombustion, pressurized oxycombustion (4 barg) respectively. CO2, CO, O2, NO, NO2and SO2emissions in the flue gas were continuously measured and recorded by an online Gasmet FTIR DX 4000 type gas analyzer. The oxy-fuel combustion experiments were done with %21 O2/ %79 CO2and %40 O2/ %60 CO2mixture. Emissions of both NOx and SO2appeared to be considerably affected by combustion atmospheres. In the oxyfuel combustion both the NOx and SO2emissions were higher than that in the air combustion and increased with increase in the O2concentration in the feed gas. In the oxyfuel combustion processes, CO2concentrations of up to 96% in the flue gases were reached on dry basis. © 2020 PCC 2020 - 37th Annual International Pittsburgh Coal Conference. All rights reserved.